A study to evaluate different conditions leading to diagnosis of T2DM in a tertiary care hospital in Eastern India - Roy, Nirmalya; Bhattacharjee, Kingshuk; Gupta, Esha (International Journal of Advances in Medicine, 2017)
Background: Diabetes is one of the most important public health problems. There is paucity of Indian data as to which conditions leads to diagnosis of T2DM. The present study endeavors to throw some light on the problem. Methods: A cross-sectional and retrospective study including 321 subjects, performed at a tertiary care hospital in eastern India. Descriptive statistical analysis has been carried out in the present study. Results on continuous measurements are presented on Mean±SD (min-max) and results on categorical measurements are presented in number (%). Significance is assessed at 5 % level of significance pooled chi-square/Fischer’s exact test used to explore association between study variables. Results: A total of 321 patients (male: female - 2.61: 1) diagnosed with diabetes over a period of 24 months were included. Mean age at diagnosis being 45.54±10.8 years respectively. Out of these, only 23.05 % presented with osmotic and other symptoms (foot ulcer, weight loss etc.) suggestive of diabetes. A substantial 43.52% of total patients were diagnosed during general healthcare check-up (35.2% in OPD and 8.32% during perioperative evaluation). Remaining patients diagnosed with diabetes included 8.28% patients admitted with acute coronary syndrome, 13.4% with infections of different types and 11.75% with other non-related diseases. Among diagnosed diabetics, 50.47% had HTN and 41.12% had IHD. Diabetic Males have higher prevalence of IHD (48.28%) than females (22.47%), p <0.001. Prevalence of HTN is higher among diabetic females (48.28%) than males (22.47%), p <0.046. The prevalence of HTN and IHD steadily increased with the increasing age group, p<0.001. Conclusions: The results of this study suggest that a very low percentage of the patients present with symptoms suggestive of diabetes. Hence, it is prudent to evaluate adult patients coming in contact with healthcare system for diabetes by simple inexpensive test.